Mobile Real-time Tracking of Acute Stroke Patients and Instant, Secure Inter-team Communication - the Join App - Stephan A. Munich; Lee A. Tan; Danilo M. Nogueira; Kiffon M. Keigher; Michael Chen; R. Webster Crowley; James J. Conners; Demetrius K. Lopes (Neurointervention, 2017)
PurposeThe primary correlate to survival and preservation of neurologic function in patients suffering from an acute ischemic stroke is time from symptom onset to initiation of therapy and reperfusion. Communication and coordination among members of the stroke team are essential to maximizing efficiency and subsequently early reperfusion. In this work, we aim to describe our preliminary experience using the Join mobile application as a means to improve interdisciplinary team communication and efficiency.Materials and MethodsWe describe our pilot experience with the initiation of the Join mobile application between July 2015 and July 2016. With this application, a mobile beacon is transported with the patient on the ambulance. Transportation milestone timestamps and geographic coordinates are transmitted to the treating facility and instantly communicated to all treatment team members. The transport team / patient can be tracked en route to the treating facility.ResultsDuring our pilot study, 62 patients were triaged and managed using the Join application. Automated time-stamping of critical events, geographic tracking of patient transport and summary documents were obtained for all patients. Treatment team members had an overall favorable impression of the Join application and recommended its continued use.ConclusionThe Join application is one of several components of a multi-institutional, interdisciplinary effort to improve the treatment of patients with acute ischemic stroke. The ability of the treatment team to track patient transport and communicate with the transporting team may improve reperfusion time and, therefore, improve neurologic outcomes.